Formulation and evaluation of fluconazole and ichthammol ointment - S. Valarmathi; M. Senthil Kumar; S. Sathish Kumar; K.P.A. Seahnaas Asmi; J.J. Dhanalakshmi; D.Stellamary (International Journal of Pharmacy and Analytical Research, 2016)
The fluconazole drug is used for treatment of anti-fungal infections like eczema, itching, pruritis. Reason for this study to formulate the ointment with different ointment bases.The ointment bases having good consistency, better diffusion, anti-fungal and antiseptic properties. Combination of fluconazole and i chthammol is used to treat the infection caused by coryne bacteria. Fluconazole and ichthammol having good anti -fungal and antiseptic property respectively. So it is used to cure the skin infection on the epidermis layer. The prepared formulation is evaluated for assay drug release, uniformity, viscosity, diffusibility, stability, permeability and other physical characteristics. Two formulations, formulation F1 and F2 were prepared with same active ingredients except different bases. Formulation F1 contains white soft paraffin, cetostearyl alcohol, light liquid paraffin and microcrystalline wax. Formulation F1 was found better than formulation F2 in all aspects like viscosity, stability, diffusibility etc.